Hepatic metastases from primary extremity leiomyosarcomas: Two case reports. Issue 18 (May 2018) - Mizoshiri, Naoki; Shirai, Toshiharu; Terauchi, Ryu; Tsuchida, Shinji; Mori, Yuki; Katsuyama, Yusei; Hayashi, Daichi; Konishi, Eiichi; Kubo, Toshikazu
Abstract: Introduction: Leiomyosarcoma is a highly malignant soft tissue sarcoma. Most leiomyosarcomas of the extremities metastasize initially to the lungs, with few metastasizing to the liver. Also, it is difficult to diagnose metastases to other regions of the lung during follow-up. Case presentation: The first patient was a 51-year-old Japanese woman diagnosed with a leiomyosarcoma of the left distal femur. She underwent chemotherapy, followed by wide tumor excision and reconstruction using frozen autograft with total knee arthroplasty. Eleven months later, a focal lesion was observed in her right liver, despite the absence of lung metastases. Partial hepatic resection was performed, and the hepatic lesion was diagnosed a metastasis of leiomyosarcoma. Two years later, there has been no evidence of local recurrence. The second patient was a 60-year-old Japanese male diagnosed with a leiomyosarcoma of the left thigh. He underwent preoperative chemotherapy followed by wide excision. Three years later, a focal lesion was found in his medial liver, despite the absence of lung metastases. Partial hepatic resection was performed, and the hepatic lesion was diagnosed as a metastasis of leiomyosarcoma. At the latest follow-up, there has been no evidence of local recurrence. Conclusions: The lung is the most common site of metastases from leiomyosarcomas of the extremeties, because these metastases are hematogenous. Both our patients presented with metastases of the liver, despite the absence of lung metastases. Hepatic metastasis is commonly found in computed tomography (CT) scan. Periodic CT scans of the chest and abdomen are necessary in following-up patients who undergo resection of primary leiomyosarcomas of the extremities.